Developing the Ability to Anticipation in Academic Activity - Vichalkovska, Nataliya; Ivanashko, Oksana (East European Journal of Psycholinguistics, 2015)
The article highlights the effectiveness of the techniques that stimulate imagination anticipative function of high school students at the Ukrainian literature lessons. The methods can enrich the student’s emotional world, his/her aesthetic experience and simultaneously contribute to his/her cognitive development. Anticipation is viewed as intellectual activity aimed at anticipatory reflection, future modeling. It helps verbalize thoughts which are aimed at clarifying unknown things. Traditional teaching methods lead to lack of imaginationm while the image function results in knowledge formalism, decreased interest in learning. The use of image  at the classes of the Ukrainian literature gives the whole process of learning meaningfulness, creative nature. It enriches the knowledge emotionally, activates the imaginative skills of students. Anticipation can be purposefully improved during training programme, which involves mastering skills in interior thinking model space of the problem solution. Among the research prospects are a study of psychological features of ontogenesis, anticipation associated with a qualitative change in cognitive and personality sphere of the students.ReferencesBatrachenko, I. (1996). Vstup do Psykholohiyi Antytsypatsiyi [Introduction to psychologyof anticipation]. Dnipropetrovsk: Dnipropetrovsk State University.Batrachenko, I. (1996). Psykholohiya rozvytku antytsypatsiyi liudyny [Psychology ofhuman anticipation development]. Dnipropetrovsk: Dnipropetrovsk State UniversityBrushlinsky, V. (1979). Myshleniye i Prognozirovaniye [Thinking and Prognostication].Moscow: Mysl, 1979.Lomov, B. (1985). Teoreticheskiye i Metodolgicheskiye Problemy Psikhologii[Theoretical and Methodological Issues of Psychology]. Moscow: Nauka.Lomov, B. (1990). Pamiat i antitsipatsiya [Memory and anticipation]. In: IssledovaniyaPamiati. (pp. 45–53). N. Korzh (ed.). Moscow: Nauka.Lomov, B., Surkov, E. (1980). Antitsipatsiya v Strukture Deyatelnosti [Anticipation inActivity Structure]. Moscow: Nauka.